The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2015
DOI: 10.1039/c5sm00760g
|View full text |Cite
|
Sign up to set email alerts
|

Helical inner-wall texture prevents jamming in granular pipe flows

Abstract: Granular pipe flows are characterized by intermittent behavior and large, potentially destructive solid fraction variations in the transport direction. By means of particle-based numerical simulations of gravity-driven flows in vertical pipes, we show that it is possible to obtain steady material transport by adding a helical texture to the inner-wall of the pipe. The helical texture leads to a more homogeneous mass flux along the pipe, prevents the emergence of large density waves and substantially reduces th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
27
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(29 citation statements)
references
References 47 publications
2
27
0
Order By: Relevance
“…The symbols denote simulation data for different particle shapes as defined in table 1, while the continuous line denote the best fit to these data using the equations, characteristics have been considered the same in all simulations since the present work is focused on the effect of particle shape. Moreover, we have also performed simulations by including tangential forces as in previous works [26,33,48,49] and found that the conclusions of the present manuscript do not change when friction is taken into account. That is, the same dissipative behavior of the granular damper is observed if friction is included, which means roughly shape-independent values of dissipated energy in the collect-and-collide regime and larger dissipation for spherical particles in the gas-like regime compared to complex particle shapes.…”
Section: Discussionsupporting
confidence: 58%
See 1 more Smart Citation
“…The symbols denote simulation data for different particle shapes as defined in table 1, while the continuous line denote the best fit to these data using the equations, characteristics have been considered the same in all simulations since the present work is focused on the effect of particle shape. Moreover, we have also performed simulations by including tangential forces as in previous works [26,33,48,49] and found that the conclusions of the present manuscript do not change when friction is taken into account. That is, the same dissipative behavior of the granular damper is observed if friction is included, which means roughly shape-independent values of dissipated energy in the collect-and-collide regime and larger dissipation for spherical particles in the gas-like regime compared to complex particle shapes.…”
Section: Discussionsupporting
confidence: 58%
“…The equations used for computing the interactions between the particles and the walls of the damper are the same used to calculate the inter-particle interaction forces, with one of the contact partners being of infinite mass and radius [33,48,49].…”
Section: Simulation Of the Granular Dampermentioning
confidence: 99%
“…Nevertheless, there are many other systems-such as particle rafts [35], pedestrian flows [36], and colloids [37]-where, commonly, the distance to the walls in the enclosure previous to the bottleneck is small and is therefore expected to affect clogging. Moreover, for the case of very narrow silos, this work raises new questions, such as if a small asymmetry of the outlet position is able to further prevent clogging or whether there is a smooth transition to a situation where the silo width equals the outlet size, i.e., the case of clogging in pipe flow [38,39].…”
Section: Discussionmentioning
confidence: 99%
“…Another modification can be inspired by the recent work [42] where angular velocity component is forced onto granular flow by spiral structures, not unlike rifling of gun barrels. If such rifling were possible in a microfluidic channel, it could also be used to induce inertial ratchet effect.…”
Section: Discussionmentioning
confidence: 99%